(untitled) (International Journal of Engineering and Computer Science, 2014)
The wireless nature of such networks allows users to access network resources from nearly any convenient location within their primary networking environment. Registered users can connect to the network from anywhere a router or another connected user is available without being identified or tracked. The onion routing network Tor is undoubtedly the most widely employed technology for anonymous web access which also gives good security for anonymous transmission of data. Wireless mesh network (WMN) is a new wireless networking paradigm. Unlike traditional wireless networks, WMNs do not rely on any fixed infrastructure. Instead, hosts rely on each other to keep the network connected. Wireless internet service provider is choosing WMNs to offer Internet connectivity, as it allows a fast, easy and inexpensive network deployment. One main challenge in design of these networks is their vulnerability to security attacks. In this paper, we investigate the principal security issues for WMNs. We study the security goals to be achieved. We identify the new challenges and opportunities posed by this new networking environment and explore approaches to secure its data communication.